Mendelian Susceptibility to Mycobacterial Diseases (MSMD) in a 13-Year-Old Ethiopian Girl with Autosomal Dominant Interferon Gamma Receptor 1(IFN-γ R1) Defect: A Clinical Diagnostic and Treatment Challenge. (23rd September 2022) - Gebeyehu, Netsanet Azene; Deribessa, Solomie Jebessa; Alexandra, Freeman; Demissie, Messay Tesfaye; Mihretu Gebre, W; Gebremariam, Aklilu Melaku; Engliz, Dagmawit Mitiku; Kidane, Tizita Yosef; Million Bekele, Lidya; Weldetsadik, Abate Yeshidinber
Abstract : Background . Mendelian susceptibility to mycobacterial diseases (MSMD) is an inborn error of immunity categorized as defects in intrinsic and innate immunity. MSMD is characterized by vulnerability to less virulent mycobacteria, such as Bacillus Calmette-Guérin (BCG) vaccine strains, as well as environmental mycobacteria (EM). The definitive diagnosis is made by genetic analysis. Treatments constitute antimycobacterial, interferon-gamma, surgery, and hematopoietic stem cell transplantation (HSCT), which is the only known curative treatment. The mortality rate ranges from 40% to 80% depending on the severity of the mutation. Case . A 13-year-old female patient had multiple hospital visits since the age of 6 months. The most striking diagnosis was repeated mycobacterial infections. She had tuberculosis affecting lymph nodes, skin and soft tissue, bone and joints, the lungs, and epidural and paraspinal regions. She has taken all the childhood vaccines, including BCG. She has been treated four times with first-line and once with second-line antituberculosis drugs. Currently, she is on treatment for nontuberculous mycobacteria and is receiving interferon-gamma. Genetic studies showed autosomal dominant Mendelian susceptibility to mycobacterial disease due to IFNG-R1 defect. Conclusion . To the authors' knowledge, this is the first case report of Mendelian susceptibility to mycobacterial diseases secondary to interferon gamma receptor 1(IFNG-R1) defect in Ethiopia. Although it has been immensely challenging, our multidisciplinary team has learned a lot from the clinical presentation, diagnosis, and management of this child.